Cathepsin S from both tumor and tumor‐associated cells promote cancer growth and neovascularization. Issue 9 (29th May 2013) - Small, Donna M.; Burden, Roberta E.; Jaworski, Jakub; Hegarty, Shauna M.; Spence, Shaun; Burrows, James F.; McFarlane, Cheryl; Kissenpfennig, Adrien; McCarthy, Helen O.; Johnston, James A.; Walker, Brian; Scott, Christopher J.
Abstract : Recent murine studies have demonstrated that tumor‐associated macrophages in the tumor microenvironment are a key source of the pro‐tumorigenic cysteine protease, cathepsin S. We now show in a syngeneic colorectal carcinoma murine model that both tumor and tumor‐associated cells contribute cathepsin S to promote neovascularization and tumor growth. Cathepsin S depleted and control colorectal MC38 tumor cell lines were propagated in both wild type C57Bl/6 and cathepsin S null mice to provide stratified depletion of the protease from either the tumor, tumor‐associated host cells, or both. Parallel analysis of these conditions showed that deletion of cathepsin S inhibited tumor growth and development, and revealed a clear contribution of both tumor and tumor‐associated cell derived cathepsin S. The most significant impact on tumor development was obtained when the protease was depleted from both sources. Further characterization revealed that the loss of cathepsin S led to impaired tumor vascularization, which was complemented by a reduction in proliferation and increased apoptosis, consistent with reduced tumor growth. Analysis of cell types showed that in addition to the tumor cells, tumor‐associated macrophages and endothelial cells can produce cathepsin S within the microenvironment. Taken together, these findings clearly highlight a manner by which tumor‐associated cells can positively contribute to developing tumors and highlight cathepsin S as a therapeutic target in cancer. Abstract : What's new? Cathepsin S is a protease that is upregulated in many types of malignant tumors. In this study, the authors examined whether cathepsin S is produced mainly by tumor cells, or by tumor‐associated cells. They found that both types of cells can contribute the enzyme. These results reveal a mechanism by which tumor cells cooperate with recruited cells to enhance tumor development. They also validate cathepsin S as a potential target to develop anti‐angiogenic and anti‐proliferative drugs.